A bottleneck-based due-date assignment methodology. (1st January 2000) - Chang, Yu-Jen; Lee, Ching-En
On-time delivery is one of the most important performance criteria in today's manufacturing systems. To enhance delivery performance, the appropriate assignment of an order's due-date is necessary. In recent years, many due-date setting methods based on regression analysis models have been proposed. Although some of them emphasise the use of shop floor information in due-date setting, the bottleneck scheduling information has not yet been taken into consideration by those methods. It is the objective of this paper to propose a new due-date assignment method based on bottleneck scheduling information. To assign an order's due-date, this proposed method first optimises the job sequence at the bottleneck using a Tabu search algorithm and then predicts the order's flow time after its completion of its bottleneck operation. Experimental results show that the proposed method can greatly enhance the delivery performance.